Regulacja taryf w sieciowych przedsiębiorstwach użyteczności publicznej - Jeżowski, Piotr (Wydział Prawa i Administracji UAM, 1994)
Network companies (telecommunication, water supply and sewage, heating, city transport) action as natural monopolies, thus practically eliminating free competition. Therefore specific Problems arise in fixing tariffs for such services and thoughtful regulations are necessary for an appropriate organization of t h e market.
Tariff regulation in public utility network companies